DECENTRALIZATION TO ACHIEVE REGIONAL INDEPENDENCE WITH COMPETITIVE ADVANTAGE AS A MODERATION - Agustina Br Surbakti; Lakharis Inuzula; Zulkarnaini; Kheriah; Yusmika Indah; Salman (CV. Radja Publika, 2025)
This study aims to analyze the influence of decentralization, competitive advantage on the level of regional independence in the Lhokseumawe City government, and measure the magnitude of the interaction between decentralization and competitive advantage on the level of regional independence in the Lhokseumawe City government. Decentralization has aspects of strong and quality resource mechanisms, to management strategies including being superior in competing. Local governments must have the right method to be able to compete, so as to fulfill aspects of healthy and sustainable competitive advantage. Referring to competitive advantage, local governments must determine the right strategy, appropriate and guarantee local governments to appear